CT of normal skulls in three categories (Female, Male, Mixed) - Heiberg, Einar; Lennartsson, Finn (AIDA Data Hub, 2021)
The data contains 300 skulls. The data is divided into three groups with 100 scans in three categories Females, Males, and Mix. The purpose of the project was to generate a machine learning algorithm to be able reconstruct missing parts of the skull for cranioplasty. Each scan was verified to ensure normal skull shape. To ensure data privacy the faces have been deblurred with an in-house developed algorithm.
Keywords: Radiology; Skull; CT; Computed tomography; Face blur; Male; Female; Medical and Health Sciences; Medicin och hälsovetenskap; Radiology and Medical Imaging; Radiologi och bildbehandling